Directors' Ownership and Firm Performance in Indonesia - Juanda . (Universitas Darussalam Gontor, 2019)
The purpose of this paper is to investigate the influence of directors’ ownership on the financial performance of firms listed on the Indonesian Stock Exchange from 2008 to 2012. The method uses quantitative approach, namely multiple linear regression. The financial performance is measured with return on assets (ROA). The research shows that directors’ ownership does not significantly influence firm performance. This implies that directors’ ownership of listed firms in Indonesia is not proven to get the interests of directors and shareholders aligned. This paper is particularly important to the policymakers and shareholders of firms in Indonesia and other developing economies since it provides a comprehensive insight into the directors’ ownership – firm performance relationship and therefore it helps them to formulate the best policies.